Bibliometric Evaluation of Scientific Journals: An Overview for Strengthening Scientific Journal Accreditation - Yoga Dwi Arianda; Riyan Arthur; Sugeng Priyanto; Irwanto Irwanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Scientific journal evaluation plays a crucial role in ensuring the quality and credibility of scientific publications. However, research mapping journal evaluation as a basis for strengthening journal accreditation is currently limited. This study aims to identify global research patterns, trends, and dynamics related to scientific journal evaluation to support the development of journal accreditation policies in Indonesia. This study used a bibliometric approach to 336 Scopus-indexed publications. Data were collected through a Scopus database search using relevant keywords as research instruments. The data were analyzed using bibliometric analysis, including publication performance, keyword co-occurrence, co-citation, and collaboration networks. The results show that journal evaluation studies have evolved from traditional bibliometric indicators, such as impact factor and citation analysis, to a multidimensional approach that emphasizes transparency, publication ethics, and open access. Furthermore, Scientometrics and the Journal of Informetrics are core journals, while China and the United States dominate global collaboration networks. This study concludes that strengthening national journal accreditation needs to be based on transparent governance, international collaboration, and measurable evaluation indicators. These findings provide an empirical basis for developing a journal accreditation system that is more credible, adaptive, and aligned with global scientific publication standards.